Pengaruh Video Edukasi Menyikat Gigi Menggunakan Media Youtube Terhadap Nilai HI Siswa Kelas IV SDN Ciburuy Kabupaten Bandung - YM, Yosi Fauziyah; Supriyanto, Irwan; Heriyanto, Yonan; Fatimah, Siti (Jurnal Terapi Gigi dan Mulut, 2024)
Successful tooth brushing depends not only on the right tools, frequency and timing of brushing, but is influenced by the educational methods used. The educational method used is audiovisual media, such as YouTube media. The purpose of this study was to examine the effect of educational videos on tooth brushing before and after the intervention. This type of research is a pre-experiment with a one group pre-test and post-test design. Sampling using total sampling technique, as many as 52 students. The variables in this study were tooth brushing education using YouTube media and Hygiene Index values. The tooth brushing education video has been tested and assessed as feasible by media and material experts. Hypothesis testing used the Wilcoxon sign ranks test. The average hygiene index score before the intervention was 0.00 and after the intervention increased to 8.50. The results of the wilcoxon sign rank test analysis showed a p-value (0.000) <0.05. The results showed that educational videos on brushing teeth using YouTube media had an effect on changes in children's oral hygiene behavior. Key words: Educational video, YouTube media, Hygiene Index.